เนี้ยะเรี๊ยด (นาคราช): มิติแห่งความสัมพันธ์เชิงสัญลักษณ์ชาติพันธุ์ - คลังฤทธิ์ สุริยา (Hatyai Academic Journal, 2017)
This article aims to present the background of the belief about Naga of the Khmer people dwelling in Phanom Dongrak mountain areas and intends to link the belief to the root of the people’s identical culture and ancestors. Khmer people in Surin province and Cambodia share the same way of life, language, beliefs, culture, and traditions. The belief about Naga, in particular, is still in their minds and soul . While Cambodians believe that Naga is their ancestor, Khmer people in Surin province believe that Naga is holy and sacred. The author wants to show how the awareness of the belief is built by both Cambodians and Khmer people in Surin and how the relational dimensions enable advantages for the two countries . Looking at it deeply, the author can function their relationships on an individual, social, and national level. Benefiting collaboration in developing relationships of the two countries, this identical relation strategy is considered as a policy enabling the unity of understanding, relationships, and harmony between Thailand and Cambodia. บทความเรื่อง เนี้ยะเรี๊ยด (นาคราช): มิติแห่งความสัมพันธ์เชิงสัญลักษณ์ชาติพันธุ์ มีจุดมุ่งหมายเพื่อชี้และแสดงให้ทราบถึงพื้นเพและที่มาของความเชื่อเกี่ยวกับนาคราชหรือเนี้ยะเรี๊ยดในแถบเทือกเขาพนมดงรัก เพื่อเชื่อมโยงเข้าสู่รากเหง้าแห่งวัฒนธรรมและบรรพบุรุษเดียวกัน ชาวเขมรสุรินทร์และชาวกัมพูชามีวิถีการดำเนินชีวิต ภาษา ความเชื่อ วัฒนธรรม ประเพณี ที่คล้ายคลึงกัน โดยเฉพาะความเชื่อเรื่องนาคราชที่อยู่ในความรู้สึกนึกคิดจากการถ่ายทอดของบรรพบุรุษดั้งเดิม เช่น ชาวเขมรกัมพูชาเชื่อว่าตนสืบเชื้อสายมาจากนาคราช อีกทั้งชาวเขมรสุรินทร์เชื่อว่านาคราชเป็นของสูง เสมือนหนึ่งสิ่งศักดิ์สิทธิ์ ความสำคัญจุดนี้เองทำให้ผู้เขียนต้องการถ่ายทอดแนวคิด เพื่อสร้างการตระหนักให้ทั้งชาวเขมรสุรินทร์และชาวกัมพูชาทราบว่ามิติความสัมพันธ์สามารถสร้างประโยชน์ให้กับทั้งสองประเทศ หากมองอย่างลุ่มลึกจะสามารถเชื่อมโยงประสานความสัมพันธ์ระดับบุคคล สังคม และระดับชาติ อันเป็นผลต่อความร่วมมือในการพัฒนาความสัมพันธ์ระหว่างประเทศ เป็นยุทธศาสตร์แห่งความสัมพันธ์เชิงอัตลักษณ์ชาติพันธุ์ เป็นนโยบายที่จะนำไปสร้างความเข้าใจ ความสัมพันธ์ ความผูกพัน ความสมัครสมานสามัคคี ความเป็นอันหนึ่งอันเดียวกัน